Marketing campaign for students from Azerbaijan to study in Czech Republic - Lebedeva, Viktoriya; Lhotáková, Markéta, 1971-; Lipavská, Markéta; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
The purpose of this bachelor thesis is to determine the advantages of Czech education system from perspective of students from Azerbaijan and propose a theoretical model of influencing their decision-making process by marketing strategies in favor of Czech Republic. In a more detailed view, the aim is to define the push and pull factors, most significant potential barriers and other factors which are taken into consideration by students from Azerbaijan while choosing a school abroad. An outcome would be to provide suggestions for improvement. I would like this thesis to be a helpful guide for future high-school graduates in Azerbaijan during their decision-making process in the period of applying for universities or exchange semesters by considering Czech Republic as the main option.
Vedoucí práce: Markéta Lhotáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses